204 Disturbed Flow Promotes Atherogenesis through the Activation of Endothelial-Mesenchymal Transition. (6th June 2015) - Mahmoud, Marwa; Kim, Rosemary; Hsiao, Sarah; Xing, Ruoyu; Heiden, Kim Van der; Mammoto, Akiko; Chen, Jing; Gauci, Ismael; Feng, Shuang; Evans, Paul
Abstract : Introduction: Atherosclerosis is influenced by local blood flow patterns, which exert wall shear stress (WSS) on endothelial cells (EC). Low, oscillatory WSS promotes atherosclerosis by inducing EC proliferation and permeability, while high WSS is athero-protective. We recently used microarray technology coupled to computational fluid dynamics to study the transcriptome of EC at regions of the porcine aorta exposed to low, oscillatory or high, unidirectional WSS. The study revealed differential expression of GATA4 and Twist1. These transcription factors can promote endothelial-mesenchymal transition (EndMT), a process that involves altered vascular endothelial (VE)- cadherin function and enhanced EC proliferation. Here we tested the hypothesis that GATA4 and Twist1 may promote atherogenesis at sites of disturbed flow by inducing EndMT. Methods and results: Quantitative RT-PCR and en face staining confirmed elevated GATA4, Twist1 and EndMT effector gene (Snail, Slug and N cadherin) expression at the inner curvature (lower WSS) compared to the outer curvature (higher WSS) of porcine and murine aortae (all p < 0.05). Snail expression at the inner curvature of the murine aorta was reduced by deletion of Twist1 in EC (Tie-2 Twist1 KO ) compared to controls (Twist1 fl/fl ; p < 0.05), demonstrating that Twist1 promotes Snail expression at a low WSS site in vivo . To establish a causal link between flow and EndMT, WSS was modified in murine carotid arteries using a constrictive cuff, the study revealed elevated Twist1 expression at the low WSS site (proximal to stenosis) and enhanced GATA4 and Snail expression at the low, oscillatory WSS site (distal). Similarly, GATA4, Twist1 and EndMT effector genes (Snail, Slug and N cadherin) were induced in porcine aortic EC (PAEC) or human umbilical vein EC (HUVEC) exposed to low, oscillatory WSS for 72h using an orbital plate system (all p < 0.05). Gene silencing demonstrated that GATA4 and Twist1 are required for Snail induction in EC exposed to low, oscillatory WSS, and chromatin immunoprecipitation revealed GATA4 interaction with promoter regions of Twist1 and Snail. Low, oscillatory WSS promoted several changes that are characteristic of EndMT including N-cadherin induction, VE-cadherin disorganisation and enhanced proliferation (all p < 0.05). Silencing of GATA4, Twist1 and Snail significantly reduced these processes and limited EC permeability (all p < 0.05) in EC exposed to low, oscillatory WSS. Conclusions: We conclude that low WSS induces EndMT and subsequent EC proliferation and permeability through the induction of GATA4 and Twist1. Our observations illuminate for the first time, the role of EndMT in arterial biomechanics and injury. Future studies should define the role of EndMT in focal atherosclerosis.